Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1038/ncponc1220
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib therapy for patients with advanced renal cell carcinoma

Abstract: Lapatinib is an oral dual inhibitor of EGFR and HER2, the coexpression of which is associated with metastatic disease in patients with renal cell carcinoma. A recent randomized phase III trial of lapatinib versus hormone therapy was conducted in patients with cytokine-refractory metastatic renal cell carcinoma and tumors overexpressing EGFR and/or HER2. The study included 416 such patients who received either lapatinib (n = 209) or hormone therapy (n = 207). No benefit in time to progression, which was the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…A Phase research veri ed that the mTOR inhibitor, temsirolimus, is another option of rst-line therapy [40]. In addition, EGFR and HER2 inhibitor lapatinib has been taken into ccRCC treatment in recent years [41]. This risk model illustrated that high risk patients were more signi cantly included in the advanced stage and grade, and they had lower IC50 level of sunitinib and temsirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…A Phase research veri ed that the mTOR inhibitor, temsirolimus, is another option of rst-line therapy [40]. In addition, EGFR and HER2 inhibitor lapatinib has been taken into ccRCC treatment in recent years [41]. This risk model illustrated that high risk patients were more signi cantly included in the advanced stage and grade, and they had lower IC50 level of sunitinib and temsirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Lapatinib is an orally administered, reversible epidermal growth factor receptor (EGFR)/human epidermal growth factor receptor 2 (HER-2) tyrosine kinase inhibitor. Clinical studies have revealed that lapatinib had promising results regarding RCC treatment 45 , 46 . The Ser/Thr protein kinase, CK2, is involved in important pathways related to tumor progression, such as Hedgehog and Wnt 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Bereits bei der ersten Interimsanalyse nach median gut einjährigem Follow-up hatte sich die Doublette der Referenztherapie bei den koprimären Endpunkten progressionsfreies (PFS) und Gesamtüberleben (OS) sowie der Ansprechrate als eindeutig überlegen erwiesen 1 . Prof. Brian Rini, Nashville (USA), stellte auf dem Annual Meeting der American Society of Clinical Oncology (ASCO) eine aktualisierte Auswertung nach längerer Nachbeobachtung von median 67,2 Monaten vor 2 . Danach verbesserte sich das PFS von 11,1 Monaten unter Sunitinib allein auf 15,7 Monate unter Pembrolizumab/Axitinib, entsprechend einer Risikoreduktion für Progress und Tod um 31 % (HR: 0,69).…”
unclassified